Plain language for interpreting in consulting rooms - H.M. Lesch (Curationis, 2007)
Intercultural communication is by nature a complex activity. In a multilingual society like ours, it will inevitably surface in the health care sector. The services of an interpreter are often considered to break the impasse in this communication process. The communication problem between the two parties, the service provider and client/ patient, is often not simply a matter of language but societal factors of which the liaison interpreter should be aware of also plays a major role for effective extended communication. This article focuses on some of the problems in rendering an oral source text in multilingual and multicultural societies such as South Africa in which there are heterogeneous target audiences for interpreting. It is pointed out that interpreters in such societies must take into account the heterogeneity of the target audiences, or otherwise interpreting will only be symbolic gestures, empty of value, and thus not communicate the message intended. In the process the limitations of the interpreter and how the presence of the interpreter can be facilitated, is also highlighted.